Heart Infinity: How Hyperconnected Ecosystems Are Adapting, Reinventing and Transforming the Digital Business Ecosystem - Vedaraju, Rajesh Kumar Bala Bhaskara (Digital Repository of Theses, 2026)
A decade ago, the world’s most valuable firms sold devices, chips, or software. Today, their power flows from something less tangible yet infinitely more transformative: hyperconnected ecosystems. These living networks dissolve traditional industry boundaries and fuse the physical, digital, and cognitive worlds into an adaptive continuum—finance with mobility, healthcare with AI, energy with semiconductors. Artificial intelligence now acts as the connective tissue of this convergence, enabling new architectures of value creation. By 2030, digital business ecosystems (DBEs) could generate US$70–100 trillion—nearly a third of global GDP (McKinsey and Company, 2023). The World Economic Forum (2023) identifies them as the new epicentre of competitiveness, where advantage stems not from ownership, but from orchestration. The scale of this transformation is unprecedented. Ten firms—Apple, Microsoft, Amazon, Alphabet, Meta, NVIDIA, Tesla, TSMC, Broadcom, and Samsung—collectively command a market capitalization exceeding US$20 trillion (CompaniesMarketCap, 2024). Several are formally designated as “gatekeepers” under the EU’s Digital Markets Act (European Commission, 2023), underscoring both their indispensability and the scrutiny they attract. Yet beneath this dominance lies a paradox: fewer than 10 percent of enterprises have successfully scaled their ecosystems (Jacobides, Cennamo and Gawer, 2018). Why do some transcend industries while others stall? What explains the persistent gulf between ambition and execution—and what hidden rhythms distinguish those who succeed? This study answers through a multi-layered empirical journey spanning ten global leaders and over one hundred executives. From 2,500 coded insights emerged HEART Infinity—a living, evidence-based operating system that unites strategy and execution in a regenerative loop. Unlike static transformation models, HEART Infinity functions as a dual-loop architecture where strategy breathes through execution and execution regenerates strategy. Its nine interdependent elements—PRISM, BADGE, STAGE, PIVOT, EPICS, EVOLVE, MODEL, SCALE, VALUE—form an infinite rhythm of sense–align–execute–learn, enabling ecosystems to evolve coherently rather than chaotically. Empirically grounded in the STAGE taxonomy, this architecture links institutional clarity, readiness, adaptability, and orchestration, transforming data into design and design into learning. The findings reveal that leadership in digital ecosystems is no longer about control but coherence—the ability to harmonize dualities such as competition and collaboration, innovation and governance, growth and responsibility. HEART Infinity reframes transformation as a living philosophy and science: a rhythm through which institutions, technologies, and people evolve together. It bridges policy and practice, strategy and execution, analytics and emotion—demonstrating that in the ecosystem era, advantage flows from orchestrating adjacency rather than owning assets. The central insight is both strategic and human: digital business ecosystems are the new operating system of the global economy, and coherence—measured not by control but by rhythm—will define the next generation of institutional and corporate leadership. HEART Infinity provides that rhythm—a way for systems to learn, leaders to orchestrate, and organizations to rediscover what it means to place heart where it truly belongs: at the centre of the infinite.